Algebraic Biology [electronic resource] : Second International Conference, AB 2007, Castle of Hagenberg, Austria, July 2-4, 2007: Proceedings - AB 2007 (2007 : Castle of Hagenberg, Austria); Anai, Hirokazu; Horimoto, Katsuhisa; Kutsia, Temur; SpringerLink (Online service) (Berlin, Heidelberg : Springer-Verlag Berlin Heidelberg, 2007)
PSZJBL